Peer Support for International Doctoral Students in Managing Supervision Relationships - Lee, Sherrie (Journal of International Students, 2017)
Doctoral education is based on a pedagogical model of apprenticeship where the expert, the more experienced academic, advises or mentors the student. Scholars have recognized the challenges of doctoral supervision due to the intense and individualized nature of the relationship. Based on the author’s personal experiences as a doctoral student and a student advocate at a university in New Zealand, this article highlights the challenges that international doctoral students face with regard to navigating the supervision relationship. The article discusses how student advocacy and peer support played an important role in resolving issues. The article concludes that peer networks are important resources for international doctoral students to make informed decisions regarding complex issues related to doctoral supervision.